Muscle-Inspired Anisotropic Aramid Nanofibers Aerogel Exhibiting High-Efficiency Thermoelectric Conversion and Precise Temperature Monitoring for Firefighting Clothing - Zhicai Yu; Yuhang Wan; Mi Zhou; Md Hasib Mia; Siqi Huo; Lele Huang; Jie Xu; Qing Jiang; Zhenrong Zheng; Xiaodong Hu; Hualing He (Nano-Micro Letters)
Highlights Muscle-inspired anisotropic aramid nanofibers thermoelectric aerogel was prepared via directional freeze-drying strategy. Resultant anisotropic aerogel exhibited high-efficiency thermoelectric conversion with Seebeck coefficient of 46.78 μV K−1 and low thermal conductivity of 0.048 W m−1 K−1. Thermoelectric aerogel-based multistage wireless high-temperature alarm system achieves a wide temperature sensing range (50–400 °C) and sensitivity response time (trigger time ~ 1.43 s) for firefighting clothing.